Variations in leaf respiration across different seasons for Mediterranean evergreen species - Catoni, R; Varone, L; Gratani, L (PHOTOSYNTHETICA, 2013)
Leaf respiration (R (L)) of evergreen species co-occurring in the Mediterranean maquis developing along the Latium coast was analyzed. The results on the whole showed that the considered evergreen species had the same R (L) trend during the year, with the lowest rates \{[\}0.83 +/- 0.43 mu mol(CO2) m(-2) s(-1), mean value of the considered species] in winter, in response to low air temperatures. Higher R (L) were reached in spring \{[\}2.44 +/- 1.00 mu mol(CO2) m(-2) s(-1), mean value] during the favorable period, and in summer \{[\}3.17 +/- 0.89 mu mol(CO2) m(-2) s(-1)] during drought. The results of the regression analysis showed that 42% of R (L) variations depended on mean air temperature and 13% on total monthly rainfall. Among the considered species, C. incanus, was characterized by the highest R (L) in drought \{[\}4.93 +/- 0.27 mu mol(CO2) m(-2) s(-1)], low leaf water potential at predawn (I-pd= -1.08 +/- 0.18 MPa) and midday (I-md = -2.75 +/- 0.11 MPa) and low relative water content at predawn (RWCpd = 80.5 +/- 3.4%) and midday (RWCmd = 67.1 +/- 4.6%). Compared to C. incanus, the sclerophyllous species (Q. ilex, P. latifolia, P. lentiscus, A. unedo) and the liana (S. aspera), had lower R (L) \{[\}2.72 +/- 0.66 mu mol(CO2) m(-2) s(-1), mean value of the considered species], higher RWCpd (91.8 +/- 1.8%), RWCmd (82.4 +/- 3.2%), I-pd (-0.65 +/- 0.28 MPa) and I-md (-2.85 +/- 1.20 MPa) in drought. The narrow-leaved species (E. multiflora, R. officinalis, and E. arborea) were in the middle. The coefficients, proportional to the respiration increase for each 10A degrees C rise (Q(10)), ranging from 1.49 (E. arborea) to 1.98 (A. unedo) were indicative of the different sensitivities of the considered species to air temperature variation.
Keywords: Drought; Leaf respiration; Mediterranean evergreen species; water stress

Relationship between net photosynthesis and leaf respiration in Mediterranean evergreen species - Gratani, L; Varone, L; Catoni, R (Photosynthetica, 2008)
The relationship between net photosynthetic (PN) and leaf respiration (R) rates of Quercus ilex, Phillyrea latifolia, Myrtus communis, Arbutus unedo, and Cistus incanus was monitored in the period February 2006 to February 2007. The species investigated had low R and PN during winter, increasing from March to May, when mean air temperature reached 19.2 °C. During the favourable period, C. incanus and A. unedo had a higher mean PN (16.4±2.4 µmol m −2 s −1 ) than P. latifolia, Q. ilex, and M. communis (10.0±1.3 µmol m −2 s −1 ). The highest R (1.89±0.30 µmol m −2 s −1 , mean of the species), associated to a significant PN decrease (62 % of the maximum, mean value of the species), was measured in July (mean R/PN ratio 0.447±0.091). Q10, indicating the respiration sensitivity to short-term temperature increase, was in the range 1.49 to 2.21. Global change might modify R/PN determining differences in dry matter accumulation among the species, and Q. ilex and P. latifolia might be the most favoured species by their ability to maintain sufficiently higher PN and lower R during stress periods.
Keywords: arbutus; cistus; Myrtus; Phillyrea; Q10; Quercus; seasonal course; temperature.

Environmental induced variations in leaf dark respiration and net photosynthesis of Quercus ilex L. - Gratani, L; Varone, L; Bonito, A (Photosynthetica, 2007)
The relationships between dark respiration rate (RD) and net photosynthetic rate (PN) in Quercus ilex L. shrubs growing at the Botanical Garden in Rome were analysed. Correlation analysis of the data sets collected in the year 2006 confirmed the dependence among the considered leaf traits, in particular, RD was significantly (p<0.05) correlated with PN (r = 0.40). RD and PN increased from March to May [1.40±0.10 and 10.1±1.8 μmol(CO2) m –2 s –1 mean values of the period, respectively], when air temperature was in the range 14.8–25.2 °C, underlining the highest metabolic activity in the period of the maximum vegetative activity that favoured biomass accumulation. On the contrary, the highest RD [1.60±0.02 μmol(CO2) m –2 s –1 ], associated to the lowest PN rates (44 % of the maximum) and carbon use efficiency (CUE) in July underlined the mobilization of stored material during drought stress by a higher air temperature (32.7 °C).
Keywords: carbon use efficiency; Leaf temperature; seasonal course

Long-time variations in leaf mass and area of Mediterranean evergreen broad-leaf and narrow-leaf maquis species - Gratani, L; Varone, L (Photosynthetica, 2006)
Morphological (dry mass, DM; surface area, LA; leaf mass per area, LMA), anatomical (leaf thickness, L), phenological (leaf life span, LL), and physiological (net photosynthetic rate, PN) leaf traits of the evergreen species co-occurring in the Mediterranean maquis developing at Castelporziano (Rome) were tested. The correlation analysis indicated that LMA variation was tightly associated with LL variations: Cistus incanus and Arbutus unedo had a short LL (4±1, summer leaves, and 11±1 months, respectively) and low LMA (153±19 g m –2 ) values, Quercus ilex, Phillyrea latifolia, and Pistacia lentiscus high LMA (204±7 g m –2 ) and long LL (22±3 months), Erica arborea, Erica multiflora, and Rosmarinus officinalis a short LL (9±2 months) and an either high (213±29 g m –2 , R. officinalis and E. multiflora) or low (115±17 g m –2 , E. arborea) LMA. LMA values were significantly (p≤0.05) correlated with PN (r≥0.68). In the tested species, LMA increased in response to the decrease of the total rainfall during the leaf expansion period. LMA variation was due to the unequal variation of DM and LA in the considered species. LMA is thus a good indicator of evergreen maquis species capability to respond to climate change, in particular to total rainfall decrease in the Mediterranean basin.
Keywords: dry mass; Erica; leaf life span; Leaf mass per area; Phillyrea; Pistacia; Quercus; RAINFALL; Rosmarinus.

Adaptive photosynthetic strategies of the Mediterranean maquis species according to their origin - Gratani, L; Varone, L (Photosynthetica, 2004)
In consideration of their origin the adaptive strategies of the evergreen species of the Mediterranean maquis were analysed. Rosmarinus officinalis L., Erica arborea L., and Erica multiflora L. had the lowest net photosynthetic rate (PN) in the favourable period [7.8±0.6 µmol(CO2) m -2 s -1 , mean value], the highest PN decrease (on an average 86 % of the maximum) but the highest recovery capacity (>70 % of the maximum) at the first rainfall in September. Cistus incanus L. and Arbutus unedo L. had the highest PN during the favourable period [15.5±5.2 µmol(CO2) m -2 s -1 , mean value], 79 % decrease during drought, and a lower recovery capacity (on an average 54 %). Quercus ilex L., Phillyrea latifolia L., and Pistacia lentiscus L. had an intermediate PN in the favourable period [9.2±1.3 µmol(CO2) m -2 s -1 , mean value], a lower reduction during drought (on an average 63 %), and a range from 62 % (Q. ilex and P. latifolia) to 39 % (P. lentiscus) of recovery capacity. The Mediterranean species had higher decrease in PN and stomatal conductance during drought and a higher recovery capacity than the pre-Mediterranean species. Among the pre-Mediterranean species, P. latifolia had the best adaptation to long drought periods also by its higher leaf mass per area (LMA) which lowered leaf temperature thus decreasing transpiration rate during drought. Moreover, its leaf longevity determined a more stable leaf biomass during the year. Among the Mediteranean species, R. officinalis was the best adapted species to short drought periods by its ability to rapidly recover. Nevertheless, R. officinalis had the lowest tolerance to high temperatures by its PN dropping below half its maximum value when leaf temperature was over 33.6 °C. R. officinalis may be used as a bioindicator species of global change.
Keywords: arbutus; cistus; drought period; Erica; Phillyrea; Pistacia; Quercus; recovery capacity; Rosmarinus; Stomatal conductance